Penulisan Berita tentang Wanita dan Pria Penjahat yang Objektif: Sebuah Discourse Analysis - Djatmika Djatmika; Zita Rarastesa (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2007)
This paper discusses about how language potrays the phenomenon of woman bandits and man bandit and their position in the news texts, which are reported by Suara Merdeka – a local newspaper whose target readers mostly reside in Central Java. Several texts were selected for the data and stylistic analysis was conducted to determine the position of the women in the action they did, which in turn show us the ideology of the journalists.Suara Merdeka is selected the source of data because this newspaper is targeted to readers residing mostly in the Javanese society, a society which a patrilineal system. In this society, crimes with women as the victims occur almost everyday, and the society sees them as something common. However, the society will react differently when a crime happens with a woman as the actor. This can be seen through the language exploitation performed by journalist in reporting the events on newspapers.